Cold creep of titanium: Analysis of stress relaxation using synchrotron diffraction and crystal plasticity simulations. (15th October 2020) - Xiong, Yi; Karamched, Phani; Nguyen, Chi-Toan; Collins, David M; Magazzeni, Christopher M; Tarleton, Edmund; Wilkinson, Angus J
Abstract: It is well known that titanium and some titanium alloys creep at ambient temperature, resulting in a significant fatigue life reduction when a stress dwell is included in the fatigue cycle. It is thought that localised time dependent plasticity in 'soft' grains oriented for easy plastic slip leads to load shedding and an increase in stress within a neighbouring 'hard' grain that is poorly oriented for easy slip. Quantifying this time dependent plasticity process is key to successfully predicting the complex cold dwell fatigue problem. In this work, synchrotron X-ray diffraction during stress relaxation experiments was performed to characterise the time dependent plastic behaviour of commercially pure titanium (grade 4). Lattice strains were measured by tracking the diffraction peak shifts from multiple plane families (21 diffraction rings) as a function of their orientation with respect to the loading direction. The critical resolved shear stress, activation energy and activation volume were established for both prismatic and basal slip modes by fitting a crystal plasticity finite element model to the lattice strain relaxation responses measured along the loading axis for three strong reflections. Prismatic slip was the easier mode having both a lower critical resolved shear stress ( τ c basal = 252 MPa and τ c prism = 154 MPa) and activation energy (Δ F basal = 10.5×10 −20 J = 0.65 eV andΔ F prism = 9.0×10 −20 J = 0.56 eV). The prism slip parameters correspond to a stronger strain rate sensitivity compared to basal slip. This slip system dependence on strain rate has a significant effect on stress redistribution to 'hard' grain orientations during cold dwell fatigue. Graphical abstract: Image, graphical abstract